Comparative evaluation of the susceptibility of neuronal (N1E-115) and non-neuronal (HeLa) cells to acetylsalicylic acid (ASA) cytotoxicity by confocal microscopy - Hernandez, M.; Kisaalita, William S. (Toxicology in vitro, 1996)
A voltage-sensitive probe, tetramethylrhodamine methyl ester (TMRM) and digital imaging (confocal microscopy) were used to quantify differential membrane potential alteration in neuronal (murine neuroblastoma, N1E-115) and non-neuronal (human epithelial-like, HeLa) cells, after 1 and 24 hr of exposure to a knownin vivo neurotoxic agent, acetylsalicylic acid (ASA), as a first step in substantiating the relevance of alteration in resting membrane potential (Vm) as a neurotoxic endpoint. After 1 hr of exposure, ASA (5.0 mm) hyperpolarized both HeLa and N1E-115 cells. Vm decreased from −57.6mV± 2.8 (n= 20cells)to−74.7mV± 1.9 (n= 20cells) and from −64.0mV± 2.1 (n= 20cells)to−82.5mV± 3.4 (n= 20cells) for HeLa and N1E-115 cells, respectively. The extent of hyperpolarization was found to be ASA concentration dependent. There was no significant difference (P < 0.05) between the cell lines with respect to ASA sensitivity, suggesting that under these experimental conditions, ASA exhibited no selective cytotoxic activity for the neuronal cells. In comparison with control cultures, 24-hr ASA (5.0 mm) exposure did not affect the surviving cell Vm. The results of the present study were inconclusive with respect to the suitability of Vm alteration as an indicator of neurotoxic potential.